Diagnosis and Treatment of Necrotizing Enterocolitis in Preterm Infants - Matniyova Zaynab Tukhtabayevna (Indonesian Journal of Innovation Studies, 2022)
Necrotic enterocolitis remains one of the main causes of morbidity and mortality mainly among premature infants with low and extremely low body weight. The percentage of newborns with necrotic enterocolitis tends to increase in recent years, which is associated with the intensive development of neonatology and resuscitation. Diagnosis in the early stages of the disease in small children is extremely difficult. Active study of the most significant diagnostic factors in the early stages of the disease is one of the first tasks of neonatologists. X-ray examination is the most reliable diagnostic method for the appearance of a clinical picture of necrotic enterocolitis. With the development of the surgical stage of the disease, the mortality rate among premature infants with extremely low body weight increases sharply. Choosing the most optimal method of surgical treatment in such children remains an important task for pediatric surgeons.